PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN SUBSEKTOR PERTAMBANGAN - Putra, Muhammad Firza Chandra (Journal of Information System, Applied, Management, Accounting and Research; Vol 8 No 4 (2024): JISAMAR (September-November 2024)DO - 10.52362/jisamar.v8i4.1645, 2024)
It is important for every company to disclose CSR because there are many climate, environmental and social gaps that are getting higher. Many investors and stakeholders assess companies in the short term, so they do not make CSR an important thing and must be considered to make decisions to invest. The company is one of the parties that must disclose CSR. CSR disclosure in the company will be presented in the company's sustainability report. Information related to finance and non-finance is one of the important things to be conveyed by the company to internal and external parties of the company. The information submitted by the company must explain the true state of the company, the company must be transparent regarding the information that will be published, so that investors can assess the company's performance properly and truthfully. This study aims to analyze the influence of independent variables, namely Profitability and Leverage, on the dependent variable, namely CSR disclosure. The data collection method used in this study is a quantitative method with secondary data obtained from the official website of the Indonesia Stock Exchange (IDX). The sample selection technique in this study was purposive sampling. The analysis model in this study is panel data regression using Eviews 10 software. The sample in this study using purposive sampling and taken in the mining sector companies coal producing subsector. Based on the results of this study found that the level of profitability affects the disclosure of CSR as well as the level of leverage affects the disclosure of CSR.